Pregnancy and post-partum outcomes of obese women after bariatric surgery: A case-control study. (May 2022) - Savastano, Giovanna; Caruso, Giuseppe; Pompeo, Damiana; Lobozzo, Benedetta; Perrone, Giuseppina; Pecorini, Francesco; Palaia, Innocenza; Muzii, Ludovico; Galoppi, Paola; Brunelli, Roberto
Highlights: Bariatric surgery (BS) reduces several obesity-related pregnancy complications. BS may increase the risk of intrauterine growth restriction and preterm delivery. BS mothers more frequently achieve the standard goal of breastfeeding for 6 months. Abstract: Introduction: Bariatric surgery (BS) is known to reduce several obesity-related complications during pregnancy, but there is concern that it may increase the risk of maternal-fetal morbidity because of the malabsorption. This study aimed to investigate the impact of restrictive BS on several pregnancy outcomes in comparison with different grades of obesity. Materials and methods: A single-center retrospective case-control study. All primiparous singleton pregnant women who underwent BS between the previous 1–5 years or with body mass index (BMI) ≥ 30 kg/m 2 delivering in our center were included. Obstetric and perinatal outcomes were analyzed and compared between the two groups. Results: Overall, 90 women were included: 30 underwent BS and 60 were obese. The mean pre-pregnancy BMI was 31.0 ± 4.2 kg/m 2 in the BS group and 38.1 ± 4.3 kg/m 2 in the control group (p < 0.001). The obese group experienced higher rate of fetal macrosomia (25% vs 6.7%; p = 0.049), gestational hypertension (23.3% vs 3.3%; p = 0.04), preeclampsia (23.3% vs 0%; p = 0.04), gestational diabetes (33.3% vs 6.7%; p = 0.01), and cesarean section (68.3% vs 20%; p < 0.0001). The BS group showed higher frequency of small for gestational age (SGA) (46.7% vs 18.3%; p = 0.006), late preterm delivery (PTD) (33.3% vs 10%; p = 0.009), cholestasis (13.3% vs 1.7%; p = 0.049). Breastfeeding ≥ 6 months was higher among BS mothers (36.7% vs 11.7%; p = 0.007). Conclusions: Our findings support the positive impact of BS on several obstetric outcomes, at the expense of a higher frequency of SGA and PTD. BS mothers more frequently achieved the recommended goal of breastfeeding for 6 months compared to obese women.